Characterization and Short-Term Outcome of Potential Celiac Disease in Children - Michal Kori; Chani Topf-Olivestone; Firas Rinawi; Raffi Lev-Tzion; Nadya Ziv-Sokolovskaya; Noy Lapidot Alon; Anat Guz-Mark; Raanan Shamir (Medicina, 2023)
Background and Objectives: Potential Celiac Disease (PCD) is defined by positive celiac serology without villous atrophy. We aimed to describe the short-term outcome of pediatric PCD while consuming a gluten-containing diet (GCD). Materials and Methods: Retrospective analysis of pediatric PCD patients continuing GCD, between December 2018–January 2022. Baseline demographics, celiac serology and duodenal biopsy results were reviewed. Follow-up data included repeated serology and biopsy results when performed. Minimum follow-up was 12 months unless celiac disease (CeD) was diagnosed earlier. Results: PCD was diagnosed in 90 children (71% females) with a mean age of 7.2 (range 1.8–16.5) years. Baseline anti-tissue transglutaminase (TTG) levels were above 10 times the upper limit of normal (ULN) in 17/90 (18.9%), 3–10 × ULN in 56/90 (62.2%) and 1–3 × ULN in 17/90 (18.9%). During follow-up, the mean time was 17.6 (range 5–35) months, TTG normalized in 34/90 (37.8%), was stable in 48/90 (53.3%), and increased or remained >10 × ULN in 8/90 (8.9%). In 20/90 (22.2%) patients, a repeat endoscopy was performed, leading to CeD diagnosis in 12/20 (60%). Thus, at the end of follow-up, CeD was diagnosed in 12/90 (13.3%). In patients with TTG >10 × ULN at diagnosis, TTG normalized in 5/17, decreased to 3–10 × ULN in 8/17, and remained above 10 × ULN in 4/17. Conclusions: During the short-term follow-up of pediatric PCD patients, less than 15% progressed to CeD. A third had normalized TTG levels, including children with TTG >10 × ULN, indicating the need for periodic serological and histological follow-up among PCD patients.